Opportunities for increasing the economic contribution of small ruminants in Asia - Devendra, C. (Australian Centre for International Agricultural Research, 1996)
The potential for increasing the economic contribution of small ruminants in Asia is discussed in the context of their wide distribution across ecosystems, value as genetic resources, productivity, significance of ownership, economic relevance, production and post-production. Approximately 57 percent and 23 percent of the total world population of 574 million goats and 1138 million sheep respectively are found in Asia. India, China, Pakistan and Bangaladesh account for about 84 percent and China, India and Pakistan 72 percent of the total populations of goats and sheep respectively in Asia. They are concentrated mainly in rainfed semi-arid and arid, and sub-humid and humid lowland and upland areas in mixed farm situations, where about 83 percent of the total small ruminant populations can be found. The significance of ownership especially by poor people, is associated with several objectives to meet short-term socio-economic needs, security and survival in which these species enable diversification of resources to reduce risks, alleviation of poverty, promotion of linkages between system components, and stability of farm households. Data are given on the nature and extent of economic contribution. The strategy for increasing this contribution is associated with involving the rainfed lowland and upland areas, increased efficiency of use of the genetic resources, targeting the poor to address spoverty, and wider use of improved technologies through community-based participation at the farm level to seek environmentally sustainable Development.